The prevalence of astigmatism among 7-year-old school children in Gua Musang district: post Covid-19 home confinement - C.S., Syarmilla; I., Nur Liyana; M.Z., Nurulain; A. A., Aznor Azwan; S., Ahmad Ziad; A.R., Suraida; I., Ismarulyusda; Abdul Rahim, Muhammad Afzam Shah (Kugler Publicarions, 2021)
Background: Uncorrected refractive error, including astigmatism remains the major cause of preventable blindness worldwide. The outbreak and spread of the coronavirus disease 2019 (COVID-19) pandemic have greatly impacted education systems worldwide. This study investigated the refractive changes and prevalence of astigmatism in 7-year-old school children in Gua Musang District post COVID-19 home confinement. Methods: In this prospective cross-sectional study, vision screening was conducted on 1832 school children aged 7-year-old, from 13 schools in Gua Musang District, Kelantan. Students that failed the screening were referred to Hospital Gua Musang and undergone cycloplegic refraction. Results: A total of 37 students [33 Malay (89.2%) and 4 Chinese (10.8%)] failed the screening (with visual acuity of less than 6/9). Gender wise, there were 18 males (48.6%) and 19 females (51.4%). The cycloplegic refraction revealed that 9 students (24.3%) had myopia with astigmatism, 14 students (37.85%) had hyperopia with astigmatism, and the other 14 students (37.85%) had astigmatism only. The prevalence of astigmatism post- COVID-19 home confinement was statistically significantly higher (X2=24.96, p<0.001) compared to pre-COVID-19 home confinement (3.5% vs 0.3%). When only the astigmatism component was analysed, all students were found to have with the-rule astigmatism, with 24 students (72.97%) having astigmatism between -1.00DC to -2.75DC, and 10 students (27.03%) having -3.00DC and above. Children with astigmatism showed significantly (X2= 1673.6, p<0.001) visual impairment (uncorrected visual acuity ≥ 6/9) compared to children with no astigmatism (97.1% vs 0.1%). Conclusion: Home confinement during COVID-19 among children appeared to cause a significant astigmatism shift in our study population. Further studies are required to reveal causal relationships with the inter-related factors of near work activity and outdoor activity time.